Development of Information and Communication Technology in Student Affairs and Personnel at Mas Insan Mulia Merangin - Rica Syofiana Sari (Greenation Computer and Information Review, 2024)
The world of education and learning in Indonesia has been greatly influenced by advances in information and communication technology. These advancements are very important and have brought about major changes in how education is run and become more innovative. However, not all groups or groups are able to respond well to such developments. Therefore, to achieve the desired results, the development of information and communication technology should be achieved through the application of information and communication technology (ICT) in education. It even includes the use of ICT as educational materials, learning aids, educational facilities, competency standards, educational administration support, classroom management tools, and educational infrastructure. This research is qualitative descriptive. Interviews, documentation and observation are data collection methods. The method for analyzing data uses qualitative analysis. Data analysis includes data reduction, display, and verification. The results of this study show that MAS Insan Mulia Merangin can use information and communication technology in terms of accepting new students, reporting learning outcomes, and supervising student discipline. In the area of staffing, there is progress in employee planning and appraisal.